A double-blind, randomized, placebo-controlled, single-center clinical trial of jiaotaiwan for the treatment of insomnia symptoms caused by disharmony of the heart and kidney - Xia, Nengzhi; Jiang, Chengrou; Zhou, Yiwei; Huang, Qun; Hu, Lufeng; Zeng, Haihuan; Luo, Lin; Yuan, Zhengzhong (Frontiers in Pharmacology, 2022)
Background: Jiaotaiwan (JTW) is a classical tranquillizing prescription in traditional Chinese medicine (TCM) for the treatment of insomnia symptoms caused by disharmony of the heart and kidney (ISDHK). This study aimed to evaluate the effectiveness and safety of JTW for treating ISDHK in a double-blind, randomized, placebo-controlled trial. Methods: From September 2018 to February 2020, 128 participants with ISDHK were included in this single-centre clinical trial. All participants were equally and randomly divided into either the JTW group (2-g JTW granules, b.i.d. for 7 days) or placebo group (2-g placebo granules, b.i.d. for 7 days). Pittsburgh Sleep Quality Index (PSQI) scores were set as the primary outcome, and polysomnography (PSG), 1H-magnetic resonance spectroscopy (1H-MRS), blood tests, and Disharmony of Heart and Kidney Scoring System (DHKSS) and clinical global impression (CGI) scores were used as secondary outcomes. Laboratory tests were used to evaluate the safety of JTW. All data were collected at baseline and posttreatment. Results: A total of 106 participants completed this clinical trial. Symptom relief was more apparent in the JTW group than the placebo group (PSQI total score: 9.34±3.578 vs. 10.98±3.073, respectively; p = 0.006). However, no PSG changes were observed between the two groups (p > 0.05). Higher CGI and lower DHKSS scores were observed after JTW treatment. Serum melatonin was increased in patients with ISDHK after JTW treatment (JTW, 339.09±256.894 vs. placebo, 219.59±169.045; p = 0.004). There were significant posttreatment differences in metabolites in the left cerebellum between the two groups (myoinositol: JTW, 13.47±2.094 vs. placebo, 12.48±2.449; p = 0.021; choline: JTW, 3.96±0.657 vs. placebo, 3.65±0.562; p = 0.008). In terms of safety, JTW had no noticeable adverse effects relative to placebo. Conclusion: JTW was safe and effective for the treatment of ISDHK. The development of large-scale trials with longer follow-up durations is recommended to provide further evidence.